How seed traits predict floating times: a biophysical process model for hydrochorous seed transport behaviour in fluvial systems. (3rd September 2015) - Carthey, Alexandra J. R.; Fryirs, Kirstie A.; Ralph, Timothy J.; Bu, Haiyan; Leishman, Michelle R.
Summary: Many plants disperse their seeds in waterbodies via hydrochoric transport. Despite a growing body of research into hydrochory, little is known about the fundamental seed traits that determine floatation ability or hydrochoric transport behaviour more generally. Seeds are transported in fluvial systems in one of three phases: surface transport, within the flow or incorporated in bedload. Seeds are often categorised as buoyant or non‐buoyant based on density, with little consideration of the morphological traits that determine how long seeds spend in each transport phase. We investigated the seed traits that best predict time spent floating under laboratory conditions, using sixty species of riparian plants from south‐eastern Australia. We measured and calculated key physical attributes (length, width, volume, surface area, mass, density, sphericity, roundness and shape category) and categorised seeds according to their primary dispersal modes (water/wind, vertebrate, adhesion, ants and unassisted). We used Cox's proportional hazards modelling to reveal that seed density and volume : surface area ratio were the physical traits that best predicted time spent floating. Volume : surface area ratio represents both seed size and shape, as it increases with size and sphericity. Our results showed that denser, larger and/or more spherical seeds (i.e. higher volume : surface area ratio) were poor floaters. They are therefore more likely to be transported in subsurface flow or as bedload. We combined our data with geomorphic models of sediment transport in flow to develop a biophysical process model of how hydrological forces and seed physical traits determine hydrochorous seed transport behaviour in rivers. The model describes how surface tension, buoyancy and flow velocity act on seed density and volume : surface area ratio to characterise time spent floating. We extrapolate from our data to conceptualise how these traits predict transitions between surface, subsurface and bedload transport. Hydrochoric seed transport behaviour and deposition are both threshold‐driven and multidirectional. Our process model is likely to be applicable across a range of different seed types in a range of rivers. It substantially increases our understanding of hydrochoric processes in rivers, lakes and lotic wetlands and will help illuminate the links between seed traits, hydrochoric transport and patterns of riparian vegetation and species composition.